Review Article: Open versus Arthroscopic Synovectomy for Pigmented Villonodular Synovitis of the Knee - E Carlos Rodriguez-Merchan (Journal of Orthopaedic Surgery, 2014)
Studies published in MEDLINE between January 2010 and October 2013 were reviewed to compare open with arthroscopic synovectomy for pigmented villonodular synovitis of the knee in terms of rates of recurrence, complication, and osteoarthritis. 10 studies specifically on this topic were analysed; all were retrospective case reports, and thus level of evidence was low. Respectively after open and arthroscopic synovectomy, the overall recurrence rates were 26.7% and 24.6%, the overall complication rates were 5.7% and 3.2%, and the overall osteoarthritis rates were 20% and 17.1%. Arthroscopic and open synovectomy did not differ significantly in terms of rates of recurrence, complication, and osteoarthritis. Prospective randomised studies are needed to confirm the findings.